2000
DOI: 10.1161/01.cir.101.22.2631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Heart Failure on Atrial Cellular and Ionic Electrophysiology

Abstract: Background-Congestive heart failure (CHF) is frequently associated with atrial fibrillation (AF), but little is known about the effects of CHF on atrial cellular electrophysiology. Methods and Results-We studied action potential (AP) properties and ionic currents in atrial myocytes from dogs with CHF induced by ventricular pacing at 220 to 240 bpm for 5 weeks. Atrial myocytes from CHF dogs were hypertrophied (meanϮSEM capacitance, 89Ϯ2 pF versus 71Ϯ2 pF in control, nϭ160 cells per group, PϽ0.001). CHF signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
300
5
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(337 citation statements)
references
References 44 publications
31
300
5
1
Order By: Relevance
“…Atrial cardiomyocytes were isolated enzymatically as previously described 18. After anesthetized with sodium pentobarbital (3%; 30 mg/kg), the heart was quickly removed from the torso and was placed in cold perfusion fluid (4°C).…”
Section: Methodsmentioning
confidence: 99%
“…Atrial cardiomyocytes were isolated enzymatically as previously described 18. After anesthetized with sodium pentobarbital (3%; 30 mg/kg), the heart was quickly removed from the torso and was placed in cold perfusion fluid (4°C).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro analyses of ion currents have shown that the minor changes in AERP observed in RVP dogs are due to inhibition of depolarizing currents being offset by the inhibition of repolarizing currents (22).…”
Section: Chronic Consequences Of Savp Versus Rvpmentioning
confidence: 99%
“…1 Congestive heart failure (CHF) is an important cause of AF and also causes ionic remodeling. 7 Like AT, CHF also decreases I to ; however, CHF-induced remodeling differs from AT remodeling in that CHF reduces I Ca to a lesser extent, decreases the slow delayed-rectifier (I Ks ), and increases the Na ϩ -Ca 2ϩ exchanger (I NCX ). 7 Consequently, instead of decreasing action potential duration, CHF leaves atrial action potential duration unchanged or increased.…”
mentioning
confidence: 99%
“…7 Like AT, CHF also decreases I to ; however, CHF-induced remodeling differs from AT remodeling in that CHF reduces I Ca to a lesser extent, decreases the slow delayed-rectifier (I Ks ), and increases the Na ϩ -Ca 2ϩ exchanger (I NCX ). 7 Consequently, instead of decreasing action potential duration, CHF leaves atrial action potential duration unchanged or increased. 7 Whereas AT-induced ionic remodeling promotes atrial reentry by decreasing the wavelength in a spatially heterogeneous fashion, 1 CHF-induced ionic remodeling increases the wavelength and may contribute to AF promotion by inducing afterdepolarization-related ectopic activity due to enhanced I NCX .…”
mentioning
confidence: 99%